PENGARUH PEMBELAJARAN DAN PRAKTIK KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI TATA BOGA SMK NEGERI 4 KOTA JAMBI - Oktaviani Oktaviani; Lili Andriani (Universitas Batanghari Jambi, 2020)
This study aims to determine the importance of the effect of learning and entrepreneurial practices on the interest in entrepreneurship in class XI SMK Negeri 4 Jambi City. There is a positive and significant influence on entrepreneurial learning and practice on the interest in entrepreneurship of class XI Catering students at SMK Negeri 4 Jambi City. This is the result of the calculation of the value of the constant coefficient of 24,077, the coefficient of entrepreneurial learning variable (X1) is 0.490, while the variable coefficient entrepreneurial practice (X2) is 0.461. So that it can be obtained multiple regression equation Y = 24,077 + 0.490 X1 + 0.461 X2. With entrepreneurial learning and practice it can build student interest in entrepreneurship. The teacher plays a very important role in directing students to achieve learning goals and students are able to develop their business well. Students can also generate self-confidence, and are ready to take all the worst risks to be able to lead a company or business.